Preparation method of optical fiber insulator
By using a liquid crystal-elastomer self-assembled sheath material system and multi-level surface treatment technology, the problems of interface stress concentration and insufficient mechanical anchoring in optical fiber insulators have been solved, improving the mechanical stability and electrical reliability of the insulators and making them suitable for extreme environments.
Patent Information
- Application Number
- CN202511170987.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-21
- Publication Date
- 2025-11-28
- Estimated Expiration
- 2045-08-21
AI Technical Summary
During long-term service, fiber optic insulators may experience insulation performance degradation and breakage risks due to problems at the material, structural, and interface levels.
By employing a liquid crystal-elastomer self-assembled sheath material system, optimizing the core rod spiral groove structure, and using multi-level surface treatment technology, the thermal expansion coefficient of the sheath material is adaptively controlled through magnetic field-induced directional alignment of liquid crystal micro-regions. Combined with spiral groove design and multi-level surface treatment, the interface durability and electrical reliability are improved.
It significantly improves the mechanical stability, environmental adaptability and electrical reliability of optical fiber insulators, making them suitable for extreme environments such as ultra-high voltage power transmission, high-altitude cold and coastal salt spray, and extending their service life.
Smart Images

Figure CN121034780A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of electrical equipment and insulator, and particularly relates to a preparation method of an optical fiber insulator. BACKGROUND
[0002] As a key component of modern power transmission system, composite insulator gradually replaces traditional porcelain insulator due to its excellent anti-flashover performance, high volume resistivity and lightweight advantage. However, it is found in long-term service that the organic silicone rubber material is easy to cause molecular chain rupture under the action of multiple stress coupling, which shows irreversible decay of hydrophobicity, umbrella skirt cracking and surface powdering, and significantly weakens the insulation performance. More seriously, this aging behavior has the characteristics of gradualness and permeability - when the sheath barrier function fails, the environmental medium (such as acid rain, salt fog) will invade the core rod interface along the microcrack channel, induce stress corrosion cracking of the glass fiber reinforced epoxy resin matrix, and finally lead to brittle fracture of the core rod. Such failures have caused many broken string accidents, which poses a systematic threat to the safety of power grid.
[0003] In order to break through the bottleneck of state monitoring, the academic circle proposes to implant a fiber Bragg grating (FBG) sensing network into the composite insulator, and realizes online diagnosis of mechanical load and insulation performance by real-time demodulation of temperature-strain dual parameters.
[0004] The existing solutions have fundamental limitations: material level: a single elastomer sheath cannot meet the requirements of low expansion rate and high toughness at the same time; structure level: equal pitch thread design leads to stress concentration at the root of the groove, inducing fatigue crack initiation; interface level: lack of multi-level protection mechanism for electrical tracking corrosion and chemical corrosion.
[0005] In view of the deficiencies of the existing design, the present application proposes a liquid crystal-elastomer self-assembly sheath material system, core rod spiral groove structure optimization and multi-level surface treatment technology. Through magnetic field induced liquid crystal micro-area directional arrangement, the thermal expansion coefficient of the sheath material is self-adaptively regulated, which significantly improves the fiber anchoring stability, interface durability and electrical reliability, and is suitable for extreme environments such as extra-high voltage transmission, high-cold and coastal salt fog. SUMMARY
[0006] The present application provides a preparation method of an optical fiber insulator, and proposes a liquid crystal-elastomer self-assembly sheath material system, core rod spiral groove structure optimization and multi-level surface treatment of the optical fiber insulator, which solves the problems of interface stress concentration, insufficient mechanical anchoring and poor long-term environmental tolerance of the optical fiber insulator caused by the difference in thermal expansion coefficient of the core rod, optical fiber and silicone rubber material.
[0007] The present application provides a preparation method of an optical fiber insulator, which comprises the following steps: spiral groove cutting is performed on the composite core rod; Based on the composite mandrel after the row helical groove cutting, the phosphating treatment, plasma activation and nano coating deposition treatment are sequentially carried out; The optical fiber and the processed composite mandrel are subjected to the lamination treatment, so that the optical fiber is laminated on the surface of the composite mandrel; The sheath assembled by pressure bonding on the surface of the composite mandrel, wherein the sheath is formed by mixing liquid crystal polymer LCP / hydrogenated nitrile rubber HNBR as the base material in a specified mass ratio to form a micro-phase separation structure, and the axial thermal expansion coefficient of the sheath is reduced to close to the mandrel by the magnetic field induced orientation process, and the radial thermal expansion coefficient is kept close to the umbrella skirt; The umbrella skirt is installed on the outside of the sheath, and the hardware fittings are installed at both ends of the composite mandrel.
[0008] The optical fiber insulator of the embodiment of the present application realizes the self-adaptive regulation and control of the thermal expansion coefficient of the sheath material by the designed composite sheath material system, the optimized thread structure and the multi-level surface treatment technology, significantly improves the optical fiber anchoring stability, interface durability and electrical reliability, and significantly improves the mechanical stability, environmental adaptability and electrical reliability of the optical fiber insulator, and can be applied to ultra-high voltage transmission, high-cold and coastal salt spray and other extreme environments.
[0009] The above description is only a summary of the technical solutions of the present application, in order to more clearly understand the technical means of the present application, which can be implemented according to the content of the specification, and in order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the following specific embodiments of the present application are described. BRIEF DESCRIPTION OF DRAWINGS
[0010] Various other advantages and benefits will become apparent to those of ordinary skill in the art upon reading the following detailed description of the preferred embodiments. The accompanying drawings are included to provide a description of the preferred embodiments and are not meant to limit the present application. Moreover, the same reference numerals are used throughout the accompanying drawings to represent same or similar components. In the drawings: Figure 1 The basic flowchart of the preparation method of the optical fiber insulator of the present application is shown; Figure 2 The mandrel processing flowchart of the preparation method of the optical fiber insulator of the present application is shown; Figure 3 The structure of the prepared optical fiber insulator of the preparation method of the optical fiber insulator of the present application is shown. DETAILED DESCRIPTION
[0011] Exemplary embodiments of the present disclosure will now be described in more detail with reference to the accompanying drawings. While exemplary embodiments of the present disclosure are shown in the drawings, it should be understood that the present disclosure may be implemented in various forms and should not be limited to the embodiments set forth herein. Rather, these embodiments are provided so that this disclosure will be thorough and complete, and will fully convey the scope of the disclosure to those skilled in the art.
[0012] This application aims to address the problems of interfacial stress concentration, insufficient mechanical anchoring, and poor long-term environmental resistance in optical fiber insulators caused by the difference in thermal expansion coefficients between the core rod, optical fiber, and silicone rubber materials. Traditional solutions, using a single-material sheath or simple bonding processes, struggle to achieve interfacial expansion matching. Furthermore, the threaded structure design is often crude, and surface treatments lack anti-aging and anti-tracking capabilities, leading to sheath cracking, fiber loosening, and insulation performance degradation. This application aims to overcome the limitations of traditional gradient CTE design by employing a microphase separation structure of liquid crystal polymer (LCP) and hydrogenated nitrile butadiene rubber (HNBR) and a magnetic field-induced orientation process. An axial magnetic field induces liquid crystal orientation in the rigid LCP chains, causing them to self-assemble into an axial nanoframework (hard region), while HNBR forms a radial elastic matrix (soft region). This achieves anisotropic control of CTE, reducing the axial CTE of the sheath to 28 × 10⁻⁶. -6 / K (close to the mandrel), radial CTE remains 90×10 -6 / K (close to the umbrella skirt) enables the control of anisotropic expansion of a single material; combined with optimized spiral groove design and multi-stage surface treatment, it solves problems related to thermal stress, fiber displacement, and environmental aging. Specifically, this application provides a method for fabricating an optical fiber insulator, such as... Figure 1 As shown, it includes: In step S101, the composite mandrel is helically grooved. In some embodiments, the composite mandrel includes an epoxy resin / glass fiber mandrel. Helically groove cutting the composite mandrel includes: By using a variable pitch design, the pitch of the spiral groove gradually changes from 1.5mm–2mm at the root of the composite mandrel to 2.5mm–3mm at the end. The spiral groove angle is controlled at 30°–45°, and the groove depth is 5%–8% of the diameter of the composite mandrel.
[0013] A gradient groove structure with a bottom is formed by cutting the composite core rod with a cutting tool. In specific examples, a diamond tool can be used for cutting, where the groove bottom width gradually expands from 0.5 mm to 1.2 mm. The gradient groove structure avoids stress concentration caused by right-angle corners. In some embodiments, after helical groove cutting of the composite core rod, the groove wall is further laser polished to remove burrs and form a smooth contour. Finally, the consistency of groove parameters is verified by CNC macro programming to ensure that a uniform mechanical anchoring interface is formed between the embedded optical fiber and the sheath material. In some examples, an Nd:YAG laser can be used for laser polishing, with the laser power set at 50W–80W and a roughness Ra≤0.8μm. This application optimizes the stress dispersion path and adapts to the difference in the expansion coefficients of the core rod and the sheath through the synergistic effect of variable pitch design and gradient groove structure, significantly improving the mechanical stability and fatigue resistance of the optical fiber insulator.
[0014] In step S102, based on the composite mandrel after spiral groove cutting, phosphating, plasma activation and nano-coating deposition are performed sequentially.
[0015] In step S103, the optical fiber and the processed composite core are bonded together so that the optical fiber is bonded to the surface of the composite core.
[0016] In step S104, a sheath is press-fitted onto the surface of the composite mandrel. The sheath is formed by mixing liquid crystal polymer (LCP) and hydrogenated nitrile butadiene rubber (HNBR) in a specified mass ratio as the matrix material to create a microphase separation structure. Through a magnetic field-induced orientation process, the axial thermal expansion coefficient of the sheath is reduced to a minimum. / K is close to the mandrel, and the radial thermal expansion coefficient remains unchanged. / K is close to the umbrella skirt, realizing the control of anisotropic expansion of a single material.
[0017] In step S105, a skirt is installed on the outside of the sheath, and fittings are installed at both ends of the composite mandrel.
[0018] The fiber optic insulator of this application achieves adaptive control of the thermal expansion coefficient of the sheath material through a designed composite sheath material system, optimized thread structure, and multi-level surface treatment technology, thereby significantly improving the mechanical stability, environmental adaptability, and electrical reliability of the fiber optic insulator.
[0019] In some embodiments, such as Figure 2 As shown, after helical groove cutting of the composite mandrel, the process also includes: The surface of the spiral groove is phosphated by immersing it in zinc-based or manganese-based phosphate solution at 60℃–80℃ for 10min–15min to form a microporous phosphate layer, which enhances the surface's mechanical anchoring ability.
[0020] Plasma activation is achieved by treating the surface with an argon / oxygen mixture at a power of 100W–150W for 5–10 minutes to generate hydroxyl and carboxyl active groups, thereby enhancing the surface chemical bonding strength. In a specific example, the volume ratio of the argon / oxygen mixture is 4:1.
[0021] Alumina or silicon nitride nanocoatings are deposited via magnetron sputtering or sol-gel methods. In some embodiments, the thickness of the nanocoating is 50 nm–100 nm, and the nanocoating is used to form a dense insulating barrier to suppress tracking and UV aging. The composite processing technology proposed in this application combines physical roughening, chemical activation, and nano-protection methods to significantly improve the weather resistance, corrosion resistance, and electrical insulation performance of the interface within the tank, and adapts to the difference in the coefficient of thermal expansion between the mandrel and sheath materials through a gradient structure design.
[0022] In some embodiments, the sheath is prepared in the following manner: A composite material is made from liquid crystal polymer (LCP) and hydrogenated nitrile butadiene rubber (HNBR) at a mass ratio of 40 parts:35 parts, with fillers as an auxiliary agent. In a specific example, the fillers include SEBS-g-MAH compatibilizer and superparamagnetic... Particles, BaTiO3 piezoelectric nanowires, and perfluoropolyether. SEBS-g-MAH compatibilizer, in 25 parts by mass, is used to bond the LCP ester bonds and HNBR cyano groups with maleic anhydride groups, forming a chemically bridging network. Three core-shell particles are used for superparamagnetic driving magnetic field orientation, inducing LCP alignment along the axial direction. Five parts of piezoelectric nanowires are used to generate charge signals under stress and monitor fiber strain in real time; two parts of perfluoropolyether are used to regulate migration to the surface to form a dynamic hydrophobic film and repair microcracks.
[0023] The matrix material and filler are mixed in an internal mixer at a temperature of 160°C and a speed of 40 rpm to form a homogeneous mixture; The mixture is injection molded into a sheath tube through a twin-screw extruder with temperature and magnetic field coordinated control. The injection temperature is controlled in three zones: 180℃ in the first stage, 300℃ in the second stage, and 240℃ in the third stage. The twin-screw extruder integrates an axial Helmholtz coil, which generates a 0.8T steady-state magnetic field at the center of the axis when DC current is applied. In this specific example, the uniformity of the magnetic field generated by the Helmholtz coil is >99%. When the temperature of the twin-screw extruder reaches 300℃ in zone two, the molten material is extruded into the die cavity under high pressure (15MPa-20MPa), activating the 0.8T axial magnetic field. Particle-driven rigid LCP chains self-assemble axially, forming a nanoframework of 150±30 nm in size, reducing axial CTE to [value missing]. / K, when the temperature reaches 240℃ in Zone 3, low-pressure filler is injected to allow the injection-molded sheath to lock in its orientation structure and reinforce its function through gradient cooling and segmented curing. In some examples, superparamagnetic particles are Core-shell structure, particle size 50–100 nm.
[0024] The gradient cooling rate is 4±1℃ / min to maintain the axially ordered structure. After cooling to room temperature, a segmented curing process is performed: 170℃ / 1 hour to activate the SEBS compatibilizer and form a "steel mesh" to bind LCP and HNBR; 120℃ / 4 hours to allow the PFPE lubricant to migrate to the sheath surface and form a waterproof membrane; and 80℃ / 2 hours to release internal stress.
[0025] The prefabricated sheath tube is heated to 120℃ to soften it. The treated composite mandrel is preheated to 100℃. A 10% SEBS-g-MAH solution is sprayed into the groove of the composite mandrel to form a chemical adhesive layer. The sheath tube is then inserted into the composite mandrel. The sheath and mandrel are pressed together by a hot-press assembly process with a pressure of 20MPa. The pressure holding stage is maintained at 120℃ for 30 minutes to promote the reaction between the compatibilizer in the sheath and the SEBS solution in the composite mandrel to form a strong bond.
[0026] This application also provides an example of the mandrel processing procedure: This example demonstrates a mandrel threading process that combines CNC technology with surface modification techniques. The specific steps are as follows: First, the epoxy resin / glass fiber composite mandrel is helically grooved using a CNC machine tool. The cutting parameters include a variable pitch design (the pitch at the root of the mandrel gradually changes from 1.5–2 mm to 2.5–3 mm at the end), a helical angle of 30°–45°, and a groove depth of 5%–8% of the mandrel diameter.
[0027] During machining, diamond-coated tools (60°–70° cutting edge angle) are used to form a gradually changing groove structure at the bottom of the groove (groove bottom width 0.5mm–1.2mm) to avoid stress concentration due to fiber bending.
[0028] The tank wall is then laser polished (Nd:YAG laser, power 50–80 W, roughness Ra≤0.8 μm) to remove burrs and pre-harden the tank wall.
[0029] The surface treatment stage sequentially completes phosphating (immersion at 60–80℃ for 10–15 minutes), plasma activation (argon / oxygen mixed gas, 100W–150W power to generate hydroxyl active groups) and nano-coating deposition to ensure that the mandrel and sheath material form a mechanical anchoring interface with high bonding strength.
[0030] This example demonstrates how the synergistic effect of gradient pitch and composite surface treatment significantly improves the fatigue resistance and environmental corrosion resistance of optical fibers in helical grooves.
[0031] Figure 3 The optical fiber insulator produced. Figure 3 The device includes a sheath 1, a silicone rubber shed 2, an optical fiber 3, and a core rod 4. The method described in this application addresses the pain points of traditional optical fiber insulators, such as sheath cracking due to interfacial thermal stress concentration, optical fiber displacement caused by insufficient mechanical anchoring, and insulation performance degradation under long-term environmental exposure, through the synergistic effect of spiral groove structure design, multi-level surface treatment, and adaptive control of the thermal expansion coefficient of the sheath material. The variable pitch and gradually changing groove structure of the spiral groove optimize the stress distribution path. Combined with the composite surface treatment technology of phosphating-plasma-nano coating, it significantly improves the interfacial mechanical locking force and electrical tracking resistance. Simultaneously, the sheath adopts an LCP / HNBR-SA self-assembly system, and the axial alignment of liquid crystal micro-regions is achieved through magnetic field induction, realizing axial CTE. / K (near the mandrel), radial CTE / K (close to the umbrella skirt). The preparation method of this application has achieved breakthroughs in the mechanical strength, interface durability and electrical performance of the sheath, and is especially suitable for extreme environments such as high temperature, salt spray and strong electric field, which greatly extends the service life and reliability of optical fiber insulators.
[0032] Table 1. Experimental results of traditional fiber optic insulators and the fiber optic insulator of this invention in different dimensions. Evaluation dimensions Traditional optical fiber insulator Optical fiber insulator of the present invention Effects achieved Mechanical stability Axial CTE 180 - 250 x 10 -6 / K fiber displacement > 0.3 mm Axial CTE 28 x 10 -6 / K, fiber displacement < 0.05 mm Thermal expansion self-adaptive matching: axial CTE close to the mandrel (difference < 7%), optical fiber anchoring force > 180 N (displacement amount decreased by 83%) Environmental durability Hydrophobicity HC4 level after salt spray 1000h, surface powdering after ultraviolet aging Hydrophobicity HC1 level after salt spray 5000h, strength retention rate 98% after ultraviolet aging Lifetime multiplication: Dynamic hydrophobic film (PFPE) + Al2O3 coating breaks the corrosion chain, lifetime extended from 20 to 35 years Electrical performance Volume resistivity 10 4 - 10 5 Ω-m Tracking resistance index ≤ 450 V Volume resistivity > 10 6 Ω-m Tracking resistance index > 650 V Insulation reliability jumps: partial discharge < 2pC (traditional > 10pC), arc resistance time > 180s (increased by 50%) Arc resistance index >650 V ≤450 V Increased by 44% Arc resistance time >180 s 120 s Increased by 50% Hydrophobicity after salt spray 5000h HC1 level HC4 level Increased by 3 levels It should be noted that, in the embodiments of this application, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes that element.
[0033] The sequence numbers of the embodiments in this application are for descriptive purposes only and do not represent the superiority or inferiority of the embodiments.
[0034] The embodiments of this application have been described above with reference to the accompanying drawings. However, this application is not limited to the specific embodiments described above. The specific embodiments described above are merely illustrative and not restrictive. Those skilled in the art can make many other forms under the guidance of this application without departing from the spirit and scope of the claims. All of these forms are within the protection scope of this application.
Claims
1. A method for fabricating an optical fiber insulator, characterized in that, include: Helical groove cutting is performed on the composite mandrel; Based on the composite mandrel after spiral groove cutting, phosphating, plasma activation and nano-coating deposition treatment are carried out in sequence. The optical fiber and the processed composite core are bonded together so that the optical fiber is bonded to the surface of the composite core. A sheath is press-fitted onto the surface of the composite mandrel. The sheath is formed by mixing liquid crystal polymer (LCP) and hydrogenated nitrile butadiene rubber (HNBR) in a specified mass ratio as matrix materials to create a microphase separation structure. Through a magnetic field-induced orientation process, the axial thermal expansion coefficient of the sheath is reduced to near that of the mandrel, while the radial thermal expansion coefficient remains close to that of the skirt. A skirt is installed on the outside of the sheath, and hardware is installed at both ends of the composite mandrel.
2. The method for preparing an optical fiber insulator as described in claim 1, characterized in that, The composite core rod includes an epoxy resin / glass fiber core rod; Helical groove cutting of composite mandrels includes: By using a variable pitch design, the pitch of the spiral groove gradually changes from 1.5mm–2mm at the root of the composite mandrel to 2.5mm–3mm at the end. The spiral groove angle is controlled at 30°–45°, and the groove depth is 5%–8% of the diameter of the composite mandrel. A composite mandrel is cut using a cutting tool to form a grooved bottom with a gradually increasing width, which gradually increases from 0.5 mm to 1.2 mm.
3. The method for preparing an optical fiber insulator as described in claim 2, characterized in that, After the composite mandrel is helically grooved, the groove walls are then laser polished.
4. The method for preparing an optical fiber insulator as described in claim 3, characterized in that, The laser polishing process uses a laser with a power of 50W–80W and a roughness Ra≤0.8μm.
5. The method for preparing an optical fiber insulator as described in claim 2, characterized in that, After helical groove cutting of the composite mandrel, the process also includes: The surface of the spiral groove is phosphated by immersing it in zinc-based or manganese-based phosphate solution at 60–80℃ for 10–15 minutes to form a microporous phosphate layer. Plasma activation is achieved by treating the plasma with an argon / oxygen mixture at a power of 100W–150W for 5–10 minutes to generate hydroxyl and carboxyl active groups. Alumina or silicon nitride nanocoatings are deposited by magnetron sputtering or sol-gel method.
6. The method for preparing an optical fiber insulator as described in claim 5, characterized in that, The thickness of the nanocoating is 50nm–100nm.
7. The method for preparing an optical fiber insulator as described in claim 2, characterized in that, The sheath is prepared in the following manner: The matrix material is composited with liquid crystal polymer (LCP) and hydrogenated nitrile butadiene rubber (HNBR) at a mass ratio of 35–45 parts: 30–40 parts, with fillers as an auxiliary agent. The matrix material and filler are mixed in an internal mixer at a temperature of 160°C and a speed of 40 rpm to form a homogeneous mixture; The mixture is injection molded into a sheath tube through a twin-screw extruder with temperature-magnetic field coordinated control. The injection temperature is controlled in three zones: zone 1 at 180°C, zone 2 at 300°C, and zone 3 at 240°C. Based on the direct current applied to the twin-screw extruder to generate a steady magnetic field at the center of the axis, when the temperature of the twin-screw extruder reaches 300°C in the second zone, the molten material is extruded into the mold cavity by a pressure of 15MPa-20MPa, and the generated steady magnetic field is activated so that the LCP rigid chains can be self-assembled into a nanoframework using the steady magnetic field. When the temperature reaches 240℃ in Zone 3, filler is injected under low pressure, so that the injection-molded sheath tube locks the orientation structure and strengthens the function through gradient cooling and segmented curing. The prefabricated sheath tube is heated until softened and then inserted into the mandrel. The sheath and mandrel are then pressed together using a hot-press assembly process.
8. The method for preparing an optical fiber insulator as described in claim 7, characterized in that, The gradient cooling rate is 4±1℃ / min; the segmented curing is 170℃ / 1h, 120℃ / 4h, and 80℃ / 2h. It also includes maintaining the softening temperature for a specified duration during the pressure holding stage to promote the reaction between SEBS-g-MAH in the sheath and the mandrel coating.
9. The method for preparing an optical fiber insulator as described in claim 7, characterized in that, The filler includes 20–30 parts of SEBS-g-MAH compatibilizer and superparamagnetic... 2–5 parts of particles, 3–8 parts of BaTiO3 piezoelectric nanowires, and 1–3 parts of perfluoropolyether.
10. The method for preparing an optical fiber insulator as described in claim 9, characterized in that, The superparamagnetic particles are Core-shell structure, particle size 50–100 nm.
Citation Information
Patent Citations
A composite insulator
CN102270530A
Optical fiber composite insulator and preparation method thereof
CN109686512A
Composite optical fiber insulator
CN114974756A
Optical fiber insulator and preparation method thereof
CN117316559A
Environmentally robust liquid crystal polymer coated optical fiber cable and its use in hermetic packaging
US20080095507A1
Cited By
Suspension type composite insulator and preparation method thereof
CN121237523A